Ethnoveterinary knowledge and practices at Colares island, Para state, eastern Amazon, Brazil - Ritter, Rhuan Amorim; Barros Monteiro, Maria Vivina; Barros Monteiro, Frederico Ozanan; Rodrigues, Silvane Tavares; Soares, Marina Lira; Ramos Silva, Jean Carlos; Correia Palha, Maria das Dores; Biondi, Germano Francisco [UNESP]; Rahal, Sheila Canevese [UNESP]; Tourinho, Manoel Malheiros (Elsevier B.V., 2012)
Ethnopharmacological relevance: The lack of ethnoveterinary surveys in Brazil, especially in the Amazon region, results in losses in the veterinary phytopharmacology field and in scientific documentation of the cultural traditions of plant use in the treatment of animal diseases.Aim of the study: To catalog, analyze and disseminate the ethnoveterinary knowledge of the inhabitants of Colares Island, Para state, eastern Amazon, Brazil.Materials and methods: A total of 72 interviews were conducted, and semi-structured questionnaires were answered by 18 men and 54 women. The data obtained were quantitatively analyzed using the informant consensus factor (ICF) and use value (UV). The plants with a reported medicinal use for domestic animals were harvested, herbalized and botanically identified.Results: Fifty-six plants, distributed in 49 genera and 35 families, were indicated to have 23 different medicinal uses, divided into six categories of use. The highest ICF (0.80) was obtained for the antiparasitic class. The Euphorbiaceae family exhibited the highest number of citations, and the species with the highest UVs were Caladium cf. bicolor, Bixa orellana, Carapa guianensis, Jatropha curcas and Cymbopogon citratus. The parts of the 56 plants that were most frequently used to prepare ethnoveterinary medications were the leaves (46%), bark (15%), roots and fruit (10%). The use of the macerated leaves was the most common method of application, used by 43% of the interviewees, and the majority of the preparations (873%) used a single plant. In addition to medicinal plants, the interviewees reported the use of products of animal and mineral origin.Conclusion: The present study contributed to the establishment of an inventory of plants used in ethnoveterinary practices in this region of the Brazilian eastern Amazon. Future phytochemical and pharmacological studies are needed to confirm the efficacy and safety of the identified plants, enabling communities to use them in a more economic, effective and safe manner. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Ethnoveterinary medicine; Medicinal plants; Zootherapy; Use value; Ethnobotany